PROSPECTIVE AND RETROSPECTIVE COHORT DESIGNS: PRINCIPLES, INDICATORS, AND APPLICATIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The cohort method stands as a cornerstone of analytical epidemiology, offering a robust framework for elucidating the temporal and causal relationships between exposures and disease outcomes. Unlike purely descriptive approaches, the cohort design integrates longitudinal observation with quantitative assessment, thereby enabling precise measurement of incidence and risk. This article provides an in-depth exploration of the conceptual foundations, methodological distinctions, and statistical tools inherent to cohort research. Emphasis is placed on the differentiation between prospective and retrospective designs, each contributing unique strengths to causal inference and data interpretation. Statistical measures—including relative risk, attributable risk, odds ratio, confidence intervals, and significance testing—are examined in the context of their epidemiological relevance and interpretive precision. The discussion extends to major historical studies, such as the British Doctors Study and the Framingham Heart Study, which exemplify the method’s transformative role in shaping public health policy and preventive medicine. Ultimately, the cohort method transcends its technical function to serve as a scientific paradigm—bridging observation and intervention, and reinforcing the evidence-based foundations of modern epidemiological inquiry.